An innovative approach for sequential extraction of phosphorus in sediments: Ferrous iron P as an independent P fraction. (15th October 2016) - Gu, Sen; Qian, Yiguang; Jiao, Yang; Li, Qingman; Pinay, Gilles; Gruau, Gerard
Abstract: Accurate identification of phosphorus (P) forms is crucially important for understanding the geochemical cycle of P; however, until now the role of ferrous iron P (Fe(II)-P) buried in sediments has been completely ignored in nearly all sequential extraction procedures developed. Using sediment cores sampled from Donghu Lake in Wuhan, China, this study explored a modified version of widely used sequential P extraction method (SEDEX;Ruttenberg, 1992 ) in which Fe(II)-P was identified as an independent fraction. Based on the high selectivity of the extractant (0.2% 2, 2′–bipyridine+0.1 M KCl) and the dissolution equilibrium of P, procedures for extracting Fe(II)-P were optimized using a 1:100 solid:liquid ratio and extraction at 50 ± 1 °C for 24 h. The sedimentary P extracted was divided into five fractions: loosely-bound P, Fe(II)-P, CDB-P, Ca-P and O-P. Fe(II)-P was the predominant fraction in fresh sediments in Donghu Lake, accounting for 15.7–49.9% of TP, with a mean of 31.6%. The mean values of Ca-P, O-P, CDB-P and loosely-bound P were 28.4%, 22.7%, 17.1% and 4.3%, respectively. Combined with component analysis of extracts and recovery experiments of standard reference minerals (vivianite, Fe3 (PO4 )2 ·8H2 O) in natural sediments, extraction of Fe(II)-P with 0.2% 2, 2-bipridine and 0.1 M KCl was robust, with a good recovery rate (88.7–100.6%) and little of the Ca-P dissolved. It is possible to use this innovative SEDEX not only to distinguish the contribution of different P matrices in fresh sediments, but also to investigate the transformation of sedimentary P under different redox conditions. Therefore, greater focus on Fe(II)-P is necessary, because it is a major sink for the geochemical process of sedimentary P. Graphical abstract: Highlights: An innovative SEDEX for anaerobic sediments was developed. Fe(II)-P was identified as an independent fraction in this innovative approach. The sedimentary P extracted was divided into five fractions: loosely-bound P, Fe(II)-P, CDB-P, Ca-P and O-P. This innovative SEDEX can also be utilized to investigate the transformation of sedimentary P during sediment oxidation.